(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this article is a more thorough examination of the specifics of the legal status of women investigators at the present stage. The main content of the study is an analysis of the regulatory framework regarding the status of a particular category of women who have decided to link their fate with military service. The article concludes with a number of proposals, the implementation of which would only improve the legal status of women military personnel.